2022
DOI: 10.3390/ijerph20010621
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Preventive Therapy for Prevention of Tuberculosis among People Living with HIV in Ethiopia: A Systematic Review of Implementation and Impacts

Abstract: Background: Tuberculosis (TB) is a major cause of morbidity and mortality in people living with HIV (PLWHIV). Isoniazid preventive therapy (IPT) prevents TB in PLWHIV, but estimates of its effects and actual implementation vary across countries. We reviewed studies that examined the impact of IPT on PLHIV and the factors influencing its implementation in Ethiopia. Methods: We searched PubMed/MEDLINE, Embase, and the Cochrane Central Register of Clinical Controlled Trials from their inception to 1 April 2021 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Consistent with previous studies finding in [ 12 , 17 , 32 , 33 , 38 , 57 60 ],concurrent administering of IPT after ruled-out of active TB symptoms with ART demoted more than 90% of active TB-associated incidence of morbidity [ 3 , 61 , 62 ]. In the final report of this systematic review and meta-analysis, it was found that HIV-infected children who did not receive IPT (preventive therapy) were at a twofold higher risk compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies finding in [ 12 , 17 , 32 , 33 , 38 , 57 60 ],concurrent administering of IPT after ruled-out of active TB symptoms with ART demoted more than 90% of active TB-associated incidence of morbidity [ 3 , 61 , 62 ]. In the final report of this systematic review and meta-analysis, it was found that HIV-infected children who did not receive IPT (preventive therapy) were at a twofold higher risk compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Heterocyclic systems play an essential role in medicinal chemistry and are related to the search for valuable new drug candidates [5,6]. One of the most biologically active cores is a six-membered pyridine ring, which is a building block found in many medicinal substances, such as sorafenib, zapiclone, isoniazid, tazarotene and bromazepam [7][8][9][10][11]. At the same time, it should be remembered that its derivatives also include nicotine, vitamin PP and the nucleotides NADH and NAD+ [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial autocorrelation is mainly applied to study the spatial correlation between geographical factors, which contains both global and local spatial autocorrelation ( Assefa, 2022 ). In this paper, we applied Moran's I index to study the regional correlation of tuberculosis in Kashgar and explored the spatial aggregation pattern of tuberculosis in the region using LISA index.…”
Section: Methodsmentioning
confidence: 99%